Legal Services and Advocacy in the Industrial Revolution 4.0: Challenges and Problems in Indonesia - Arifin, Ridwan (Universitas Negeri Semarang, 2020)
THE INDUSTRIAL revolution 4.0 had a significant influence in various sectors, including the law enforcement sector. Law enforcement, legal aid, legal services and advocacy in the industrial revolution 4.0 era have their own characteristics of challenges. This edition of the Indonesian Journal of Advocacy and Legal Services raises the theme of Legal Services and Advocacy in the Industrial Revolution 4.0 in the hope of providing a new picture, discourse, and treasury in the provision of services and legal assistance, advocacy and community assistance.